Optimization of fertilizer doses for increased fruit yield of dragon fruit adopting response surface methodology and Box-Behnken design - Karunakaran, Ganesan; Ramachandran, Sundram; Venugopalan, Rangarajan; Selladurai, Rajendiran; Arivalagan, Manivannan; Srivastava, Anoop Kumar; Shilpa, Kanakanahalli Gangadharappa; Ruchitha, Thimmarayappa (Frontiers in Plant Science, 2025)
Dragon fruit stands out all among fruits not only for its essential nutrients and antioxidant content but also for its aesthetic appeal. Its high demand in consumer preferences and marketing values makes it a sought-after fruit. However, its production is limited by poor agronomic practices, particularly suboptimal use of fertilizers. Therefore, this study aims to enhance dragon fruit production by improving fertilizer use efficiency, thereby increasing fruit yield without wastage of inorganic fertilizer. To achieve this objective, two dragon fruit pulp types, white and purple-red, were chosen as test crops, and a total of three independent variables with different graded levels of N:P:K combinations were utilized. Second-order rotatable design (SORD) particularly Box-Behnken design (BBD) was employed using response surface methodology (RSM) to fix the fertilizer treatment combinations, to study the yield response and optimization of fertilizer doses. The response outcomes of white pulp fruit yield per hectare (Y1) and purple red pulp fruit yield per hectare (Y2) of dragon fruit were predicted and verified for model adequacy. The results indicated that optimum fertilizer doses (N:P2O5:K2O) of 400:300:650 g/pillar/year and 700:400:350 g/pillar/year for white and purple red pulped dragon fruit, respectively, led to a desirable effect, resulting in maximum yields of 25.5t ha-1 and 35.6t ha-1 for white and purple red pulped dragon fruit, respectively.